Enhancing learning outcomes and work readiness through knowledge sharing and training transfer: a qualitative study of sales promoters - Marjani, Marjani; Murini , Murini; Hasddin, Hasddin; Mirad , Mirad; Lasitiha, Hasmirawati Injar (Jurnal Konseling dan Pendidikan, 2025)
In informal work environments, such as frontline sales promotion, workplace learning often occurs outside formal training channels. However, limited research has examined how knowledge sharing and training transfer affect individual preparedness for real-world work challenges. This study aims to analyze the role of knowledge sharing and training transfer in enhancing learning outcomes and work readiness among sales promoters at PT Unilever in Kendari City. Employing a qualitative descriptive approach, the research involved 25 participants—22 sales promoters, one supervisor, one coordinator, and one beauty advisor. Data were collected through in-depth interviews, observation, and document analysis, and analyzed using Miles and Huberman’s thematic coding technique. The study found that knowledge collecting occurred through informal peer learning and semi-structured supervisor-led sessions, reflecting principles of adult education and social cognitive theory. In contrast, knowledge donating was inconsistent, hindered by emotional disengagement and lack of organizational support. Training transfer was not automatic and required ongoing peer reinforcement, motivation, and contextual alignment to workplace demands. Learning in this setting is relational and emotionally mediated. Embedding counseling-based strategies such as peer mentoring, reflective dialogue, and feedback mechanisms into training programs can enhance individual development and organizational performance. This study contributes to the counseling and vocational education literature by emphasizing the importance of psychosocial support in knowledge transfer and learning continuity within informal employment settings.